Automatic Generation of Data Conversion-Programs Using a Data Description Language (DDL). Volume I. System Description and Documentation. - Ramirez,Jesus Arturo (1973)
The report describes a DDL/DML Processor and a methodology to automatically generate data conversion programs. The Processor accepts as input descriptions of source and target files in a Data Description Language (DDL) and a Data Manipulation Language (DML). It produces an output conversion IBM 370/165 program in PL/1 capable of converting the source file and producing the target file. (Author) See also Volume 2, AD-761 161.